PENGARUH KUALITAS PELAYANAN DAN PENERAPAN MUDHARABAH TERHADAP KEPUASAN NASABAH PADA BANK BRI SYARIAH TANGERANG SELATAN - Muhammad Sopiyana (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
For banks, providing satisfaction is the main way to achieve profit. So, all efforts are made including the products and services being sold. This research was conducted with the intention of finding out how strong services and products (mudharobah) can increase customer satisfaction. This research method uses quantitative mentode. By using primary data to know the variables of service and application mudharobah able to influence satisfaction. Quantitative approach is used to examine certain populations or samples, The method used in sampling in this study is by non probability sampling using convenience sampling techniques. Data collection techniques using quisioner methods, literature studies (Library Reseacrh), quantitative or statistical data analysis with the aim of testing the established hypothesis. The results showed that satisfaction could be explained by the service and the mudharobah transaction model. The interesting thing from the research results is that the concept of mudharobah is the dominant variable in influencing customer satisfaction